Si Duglit: ang dugong makulit - Gatmaitan, Luis (Manila : Hiyas Children's Collection, 1995)
How important is a blodd cell to a man's life? This was discovered by Duglit, the youngest blood cell inside Mang Omeng's body.
Keywords: Health-Juvenile literature